2018
DOI: 10.1038/s41598-018-23688-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tactile sensory deterioration amongst the elderly

Abstract: It is known that roughness-smoothness, hardness-softness, stickiness-slipperiness and warm-cold are predominant perceptual dimensions in macro-, micro- and nano- texture perception. However, it is not clear to what extent active tactile texture discrimination remains intact with age. The general decrease in tactile ability induces physical and emotional dysfunction in elderly, and has increasing significance for an aging population. We report a method to quantify tactile acuity based on blinded active explorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 55 publications
1
66
0
Order By: Relevance
“…Furthermore, the flattening of the DEJ appears to redistribute these stresses away from the junction [180], which is the location of many mechanoreceptors. This result would suggest that changes in skin geometry may play an important part in the deterioration of tactical perception experienced by the elderly described by Skedung et al [178]. Earlier, similar findings were obtained in a comparable three-dimensional finite element study conducted by Garcia-Martinez and Limbert [181] which was later extended [182].…”
Section: Skin Sensing Abilitiessupporting
confidence: 76%
See 3 more Smart Citations
“…Furthermore, the flattening of the DEJ appears to redistribute these stresses away from the junction [180], which is the location of many mechanoreceptors. This result would suggest that changes in skin geometry may play an important part in the deterioration of tactical perception experienced by the elderly described by Skedung et al [178]. Earlier, similar findings were obtained in a comparable three-dimensional finite element study conducted by Garcia-Martinez and Limbert [181] which was later extended [182].…”
Section: Skin Sensing Abilitiessupporting
confidence: 76%
“…Tactile perceptual ability is known to decline with age [177][178][179]. As pointed out by Skedung et al [178], besides physical dysfunction, the loss of tactile ability for the elder ly also features an important emotional dimension, and both aspects will gain increasing importance as populations continue to age. As people age and aspire to remain active longer, it is likely that the role of skin-to-skin contact in intimate physical relationships will become an area of importance for many more individuals.…”
Section: Skin Sensing Abilitiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Increased brain metabolites of the white matter are related to altered energy metabolism. Previous studies suggested that, along with aging, there was a reduction in the number of nerve cells in the brain and the number of receptors under the skin (Nalbant, 2008;Kalisch, Tegenthoff & Dinse, 2008;Skedung et al, 2018). Most of the studies showed that functional and structural changes in the nerve fibers, thalamus, and cortex occur with aging (Sato, Sato & Suzuki, 1985;Katzman, 1992;Verdú et al, 2000;Kemp et al, 2014).…”
Section: Discussionmentioning
confidence: 99%